En Gotlandsk landsbykirkes portalikonografi : Om en tids religiøse ikonografi og dens kunstner - Sparre, Torben (Kirkehistoriske Samlinger, 1990)
The above paper presents and discusses the door-sculptures of Norrlanda church on Gotland, considered as representative of the sculptural art of the so-called Aegypticus, a stone-master and architect who worked here during the period c. 1335-40. At Norrlanda, the master has treated a series of New Testament themes in the style called »countergothic«; the sculptures are presented in the article with a strong emphasis on their function as conveyors of a religious message.